Initiation of Surveillance for Fetal Growth Restriction: At Time of Diagnosis or at 32 Weeks? [A230]. (May 2022) - Vadlamudi, Gayathri D.; Hinge, Amita M.; Goyert, Gregory; Shaman, Majid
Abstract : INTRODUCTION: Following the 2020 Society for Maternal–Fetal Medicine guideline on management of fetal growth restriction (FGR), our institution began initiating antenatal surveillance at time of FGR diagnosis instead of at 32 weeks of gestation. METHODS: This institutional review board‒approved retrospective cohort study included patients with FGR, without absent or reversed end diastolic velocity in umbilical artery Dopplers, from the 12-month periods preceding and following this change in surveillance. Previously, twice-weekly non-stress testing (NST) was initiated at 32 weeks of gestation. Subsequently, surveillance was initiated at time of FGR diagnosis, with weekly biophysical profile (BPP) starting at 26 weeks and additional weekly NST at 32 weeks. The primary outcome was a composite of neonatal intubation, respiratory distress syndrome, intraventricular hemorrhage, and perinatal death. Secondary outcomes were rates of neonatal intensive care unit (NICU) admission, preterm delivery, surveillance visit attendance, and referral for further monitoring. RESULTS: A total of 150 patients were studied: 73 with antenatal testing initiated after 32 weeks and 77 with testing starting at time of diagnosis. There was no difference in primary neonatal composite outcome (6.8% versus 9.1%, P =.766), rates of NICU admission (19.2% versus 18.2%, P =.876), preterm delivery (16.4% versus 16.9%, P =.942), surveillance visit attendance (91.7% versus 88.9%, P =.697), or overall referral rate for further monitoring (8.0% versus 8.2%, P =.894). With initiation of surveillance at time of diagnosis, 7.5% of referrals occurred prior to 32 weeks. CONCLUSION: In the setting of FGR with normal Dopplers, initiating antenatal surveillance at time of diagnosis led to increased referrals for further monitoring at earlier gestational ages without improvement in neonatal outcomes.